2013
DOI: 10.5216/ree.v15i4.19127
|View full text |Cite
|
Sign up to set email alerts
|

Cotidiano medicamentoso de adolescentes com HIV/AIDS

Abstract: No presente estudo foi objetivo descrever as características sociodemográficas, clínicas, comportamentais e do cotidiano medicamentoso de adolescentes com HIV/AIDS de 13 a 19 anos atendidos em serviço de referência. Estudo transversal descritivo com abordagem quantitativa realizado com 23 adolescentes. Os dados foram coletados por meio de formulário nos dias de consulta no ambulatório. A análise univariada evidenciou o quantitativo do sexo feminino, a fase inicial da adolescência e a transmissão vertical.Desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A total of 23 adolescents took part in the study. Data collection occurred between September 2011 and March 2012, by means of structured interviews, with the use of validated form 15 which included: questions about demographic, social, clinical, pharmacological and behavioral data of the participants and folder containing illustrations of antiretroviral (ARV) drugs for adolescents to identify what they are and how to use them 10,11 . Collection was on Tuesdays and Thursdays, days of consultations of adolescents with HIV/AIDS, and the meeting took place individually, in a private room.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 23 adolescents took part in the study. Data collection occurred between September 2011 and March 2012, by means of structured interviews, with the use of validated form 15 which included: questions about demographic, social, clinical, pharmacological and behavioral data of the participants and folder containing illustrations of antiretroviral (ARV) drugs for adolescents to identify what they are and how to use them 10,11 . Collection was on Tuesdays and Thursdays, days of consultations of adolescents with HIV/AIDS, and the meeting took place individually, in a private room.…”
Section: Methodsmentioning
confidence: 99%
“…As it could not be in a study of people in this age group, the study encountered ethical aspects related to the participation of adolescents in research, involving information about their diagnosis, often hidden in the family, and issues related to sexuality and knowledge of a disease that remains, even today, stigmatized 11 . Ensuring the ethical aspects is of utmost importance in the study, because they will be the ones who will protect and ensure the confidentiality and secrecy of information provided by the participant.…”
Section: Ethics In Research On Adolescents Living With Hiv/aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the positive aspects, many barriers were perceived by family members. A similar study found that, besides the caregivers having to face the disease and the treatment, they had to overcome the barrier of the patient's aggressiveness and his disobedience (11) . The virus-infected in moments of anger can develop aggressive behavior, compromising the relationship with the caregiver.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the different stages of cognitive maturity can lead to curiosity, questioning, negative psychological reactions and dissemination of their serological status to different people, generating prejudice and discrimination. On the other hand, the family has difficulty exposing their life history with fears, guilts and unpreparedness to face the situation (11) .…”
Section: Discussionmentioning
confidence: 99%